2019
DOI: 10.1016/j.ebiom.2019.05.050
|View full text |Cite
|
Sign up to set email alerts
|

(Epi)genetic regulation of CRTC1 in human eating behaviour and fat distribution

Abstract: Background In brain, CREB-regulated transcription co-activator 1 (CRTC1) is involved in metabolic dysregulation. In humans a SNP in CRTC1 was associated to body fat percentage and two SNPs affected RNA Pol II binding and chromatin structure, implying epigenetic regulation of CRTC1 . We sought to understand the relevance of CRTC1 SNPs, DNA methylation and expression in human eating behaviour and its relationship to cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…ITPR3 is known as well for process of sensory perception of taste. CRTC1 gene in human has highest transcript expression in brain compared to other tissues and is known for affecting eating behavior [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…ITPR3 is known as well for process of sensory perception of taste. CRTC1 gene in human has highest transcript expression in brain compared to other tissues and is known for affecting eating behavior [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we used the Leipzig Obesity cohort, which has been previously described in detail 2 18–20. Briefly, the cohort contains lean, overweight and obese subjects from whom intraindividually paired samples of SAT and OVAT were taken during bariatric surgery or other procedures such as cholecystectomy.…”
Section: Methodsmentioning
confidence: 99%
“…It is now being increasingly recognized that obesity results from a complex interplay between genetics and environmental factors and that epigenetic processes may constitute a physiological mechanism by which these genetic and environmental factors interact [2,3]. Recent studies in individuals with obesity indicate that various genes implicated in both metabolic regulation and brain function may be involved [2,3]. As such, the CREB regulated transcription coactivator 1 (CRTC1) – an important mediator in the hypothalamus of the effects of hormones and nutrient signals on energy balance [4] – is an interesting candidate for improving the understanding of molecular mechanisms of obesity.…”
mentioning
confidence: 99%
“…Interestingly, animal studies have shown that (unlike other CREB co-activators such as Crtc2) Crtc1 is primarily expressed in the brain [4,8]. The various associations reported by Rohde et al [3] with blood and adipose tissue-based (epi)genetic measures of CRTC1 are in line with the obese phenotype observed in Crtc1 knockout mice [4,8]. Yet, as DNA methylation cannot be assessed directly in the living human brain, an important avenue for future work is the use of animal models of obesity to validate current methylation findings in brain tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation